2018
DOI: 10.1155/2018/3039061
|View full text |Cite
|
Sign up to set email alerts
|

Application of Federal Kalman Filter with Neural Networks in the Velocity and Attitude Matching of Transfer Alignment

Abstract: The centralized Kalman filter is always applied in the velocity and attitude matching of Transfer Alignment (TA). But the centralized Kalman has many disadvantages, such as large amount of calculation, poor real-time performance, and low reliability. In the paper, the federal Kalman filter (FKF) based on neural networks is used in the velocity and attitude matching of TA, the Kalman filter is adjusted by the neural networks in the two subfilters, the federal filter is used to fuse the information of the two su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Features (Ra, Rz, Ry) are only the statistical average of surface morphology with a lot of information loss. The standards of DIN EN ISO 4287 and ASME B46.1 give more explicit and more information of surface morphology using four features, which are surface rugosity, standard deviation, skewness, and kurtosis [39,41,42], presented in (10)- (13). But these features still cannot work on all the pixels of surface morphology and cannot give a significant and systematic description statistics.…”
Section: Prediction Model Of Controller Parameters Of Grindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Features (Ra, Rz, Ry) are only the statistical average of surface morphology with a lot of information loss. The standards of DIN EN ISO 4287 and ASME B46.1 give more explicit and more information of surface morphology using four features, which are surface rugosity, standard deviation, skewness, and kurtosis [39,41,42], presented in (10)- (13). But these features still cannot work on all the pixels of surface morphology and cannot give a significant and systematic description statistics.…”
Section: Prediction Model Of Controller Parameters Of Grindingmentioning
confidence: 99%
“…The predictive controllers are designed for behaviour predicting of electronic circuits [8], trajectory tracking [9], trajectory tracking of underactuated surface vessels [10], performing attitude tracking control of a quad tilt rotor aircraft [11], and tracking error converging to a neighborhood of the origin [12]. A federal Kalman filter based on neural networks is used in the velocity and attitude matching of transfer alignment [13]. An iterative neural dynamic programming is provided for affine and nonaffine nonlinear systems by using system data rather than accurate system models [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cam-shift algorithm is the commonly used gesture tracking algorithm, which is good for tracking solid objects in a black-and-white background. However, the contrast between the background color and the target is not obvious, and the tracking effect is poor [15][16][17][38][39][40]. To verify the effectiveness of the switching federated filter algorithm, a gesture tracking and positioning experiment based on the 3D interactive software is presented.…”
Section: Gesture Tracking and Positioning Experiments Based On D Imentioning
confidence: 99%
“…All of these algorithms have their own advantages and disadvantages and are proposed for specific noise. In practice, a variety of noise generation methods have demonstrated that a single filtering algorithm cannot be effective for all types of image filtering [1][2][3][4][5][6]. In the case of the filter system based on Kinect sensor depth image, light intensity and sensor temperature are the main factors that generate the noise in the image.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the filter system based on Kinect sensor depth image, light intensity and sensor temperature are the main factors that generate the noise in the image. In addition, the short stay at the time of image formation and the interference of the channel during image transmission are also the main reasons for the noise generation [3]. Among these noises, Gaussian noise and the saltand-pepper noise are the two most important types of noise.…”
Section: Introductionmentioning
confidence: 99%